2007
DOI: 10.1093/glycob/cwm026
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of galectin-8 and its carbohydrate recognition domains for ligands in solution and at the cell surface

Abstract: Galectin-8 has two different carbohydrate recognition domains (CRDs), the N-terminal Gal-8N and the C-terminal Gal-8C linked by a peptide, and has various effects on cell adhesion and signaling. To understand the mechanism for these effects further, we compared the binding activities of galectin-8 in solution with its binding and activation of cells. We used glycan array analysis to broaden the specificity profile of the two galectin-8 CRDs, as well as intact galectin-8s (short and long linker), confirming the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
237
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(263 citation statements)
references
References 49 publications
24
237
1
1
Order By: Relevance
“…Previous in-depth studies of GAL8 showed that its N-CRD is a really unique domain for recognizing sulphated and sialylated sugars 19,28,29 . In our structure, the diphosphate moiety attached to the pentose ring in NAD binds to the sugar-binding site of N-CRD specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in-depth studies of GAL8 showed that its N-CRD is a really unique domain for recognizing sulphated and sialylated sugars 19,28,29 . In our structure, the diphosphate moiety attached to the pentose ring in NAD binds to the sugar-binding site of N-CRD specifically.…”
Section: Discussionmentioning
confidence: 99%
“…haptoglobin so far, but this does not rule out Carlsson et al, page 14 that they exist in a fraction of it. Alternatively, galectin-8N binds NeuAcα2-3Galβ1-3GlcNAc, which it also prefers over the galectin-1 binding NeuAcα2-3Galβ1-4GlcNAc [20], and which may occur in N-glycans. Hence, galectin-1 and -8N may be detecting the balance between two different glycosylation features, which in turn would be determined by the activity of glycosyltransferases typical for the cell making the glycoprotein and further regulated by surrounding pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In another study we found that the N-terminal carbohydrate recognition domain (CRD) 1 of galectin-8 (galectin-8N) binds significantly more glycoproteins, including haptoglobin, in sera of patients with IgA-nephritis (IgAN) compared to patients with other forms of kidney disease and healthy subjects [18]. Galectin-8N has a strong preference for 2-3 sialylated galactosides [20][21], and its binding of serum glycoproteins requires the presence of 2-3 sialic acid [18], in contrast to the case of galectin-1, suggesting a different binding site.…”
Section: Introductionmentioning
confidence: 99%
“…The CRDs of diff erent galectins and even the N-terminal or C-terminal CRDs of tandem repeat galectins display variations which serve to engage different subsets of functionally distinct glycoproteins (Hirabayashi et al, 2002;Ideo et al, 2003;Patnaik et al, 2006;Stillman et al, 2006;Carlsson et al, 2007;Stowell et al, 2008;Ideo et al, 2011). Thus, understanding the functions of a particular galectin requires defi ning the range of its interacting elements in diff erent cellular contexts.…”
Section: Introductionmentioning
confidence: 99%